Institutional support of Finnish universities : Bangladeshi students’ experiences - Sadaf (2019)
This paper examines Bangladeshi students’ reasons of feeling anxious when they go abroad for higher education and their perception on institutional support that helps them in managing anxiety which eventually leads to effective communication. As international student population cannot be considered as one homogeneous group, studying Bangladeshi students’ perceptions and viewpoints brought out interesting insights.